INVESTIGATION OF CONCRETE DURABILITY WITH FLY ASH AS A SUBTITUTION OF A FEW CEMENT TO CLORIDE ÃâÃâ ATTACK - BAHRI AHMAD (NIM : 25008034); Pembimbing : Ivindra Pane, ST.,MSc.,MSE.,PhD., SYAMSUL
Concrete durability to environmental condition where the concrete is placed without occuring damage until a planned time poses the very important case. In several cases, no a little cost must be used to improve a destroyed structure because of attack of hazardous substances. The concrete employed at the sea environment is very potential to meet damage because of cloride – attack, sulfate and the other anorganic cloride acid. The level of occured damage is depend on the concrete ability to prevent penetration of the materials into the concrete. One of the efforts result in the good durability of concrete at the sea environment is to make concrete more impermeable to water. Water constitutes a very effective medium to enter the dangerous materials into concrete. The usage of especial cement such as V type of cement also become an alternative for the concrete at the sea environment. The usage of additional material of fly ash proposes to decrease cement usage as well as to increase cement density. This research intends to identify the cement durability to cloride – attack with cement type of PCC and V type based on fly ash. The reached pressure strength of the concrete varies from 35 Mpa to 52 Mpa. Cloride induction into concrete constitutes slow process. Therefore, laboratory test is performed accelerated by using electric field to force cloride ion penetrate into the concrete. This method has become test standard of cloride penetration into the concrete in Europe called Nordic Test Build 492 (Rapid Migration Test). In addition, porosity test is performed as well as the level of water absorption or sorptivity is done as two cases correlating with water penetration into the concrete. The research results show that the concrete of V type of cement based on fly ash 11,65% has the required strength and durability. The concrete of PCC cement and V type of cement based on the same fly ash of 26,3%, PCC cement shows the better durability performance to cloride – attack. Both of this composite are encouraged for the concrete at the sea environment with the pressure strength of 35 Mpa and 44 Mpa, respectively. The concrete of PCC cement without fly ash with the pressure strength of 39 Mpa is not recommended for the concrete of the sea environment.